FREQUENCY OF DIFFERENT TYPES OF VERNAL KERATOCONJUNCTIVITIS IN PATIENTS PRESENTING TO A TERTIARY CARE HOSPITAL - Irfan, Muhammad; Khan, Shahid Abdur Rauf; Ullah, Wali; Ahmed, Zeeshan; Khalid, Kamran (Journal of Postgraduate Medical Institute, 2021)
Objective: To determine frequency of different types of vernal kerato-conjunctivitis presenting to ophthalmology department of Hayatabad Medical Complex, Peshawar. Methodology: This was a cross sectional study. A total of 165 patients were examined through slit lamp and diagnosed as vernal kerato-conjunctivitis on the basis of pre-determined criteria. After diagnosis, they were classified into the three types. Percentages were calculated for the types of vernal kerato-conjunctivitis in each group. Data was stratified among different age groups and gender. Chi-squared test was used to calculate the significance for these categorical variables. Results: Out of 165 patients, 105 were male and 60 were female. Age ranged from 5-16 years with mean ± SD of 9 ± 2.8 years. Average duration of symptoms was 4 ± 1.6 years. Age group of 9-12 years had highest number of patients which was 66 (40%) while the lowest number of patients were observed in age group 13-16 years that was 41 (25%). Palpebral vernal kerato-conjunctivitis was the most frequent type of VKC seen in children which 47%, limbal was 30% and mixed type was seen in 23%. Conclusion: Vernal kerato-conjunctivitis was more frequent in male gender while palpebral type was the most common presentation in our studied population.